Measuring Household Usage of Financial Services : Does it Matter How or Whom You Ask? - Cull, Robert; Scott, Kinnon (World Bank, 2012)
In recent years, the number of surveys on access to and use of financial services has multiplied, but little is known about whether the data generated are comparable across countries or within the same country over time. A randomized experiment in Ghana tested whether the identity of the respondent and the inclusion of product-specific cues in questions affect reported rates of use of financial services. Rates of household use are almost identical whether the head reports on behalf of the household or whether the rate is tabulated from a full enumeration of household members. A less complete summary of household use of financial services results when randomly selected informants (nonheads of household) provide the information. For credit from formal institutions, informal sources of savings, and insurance, reported use is higher when questions are asked about specific financial products rather than about the respondent's dealings with types of financial institutions. In short, who is asked the questions and how the questions are asked both matter.